The Influence Of Fanpages Following Instagram On Intention To Transact With Sense Of Brand Community And Brand Love Mediators In Digital Financial Companies - Alfiani, Dewi Fortuna; Fadli, Jul Aidil (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Social media has given consumers the opportunity to speak up for the products or services they sell and consume. In recent years, the social networking site Instagram is one of the most popular social networking sites for consumers. One of the most widely used platforms by companies for Instagram marketing is